Gender associated with the intention to choose a medical specialty in medical students: a cross-sectional study in 11 countries in Latin America - Ng-Sueng, Luis Fernando (2016)
Introduction: The selection of a medical specialty has been associated with multiple factors, such as personal preferences, academic exposure, motivational factors and sociodemographic factors, such as gender. The number of women in the medical field has increased in recent years. In Latin America, we have not found any studies that explore this relationship. Objective: To determine whether there is an association between gender and the intention to choose a medical specialty in medical students from 11 countries in Latin America. Methods: Secondary analysis of Latin American Collaborative Research Group in Human Resources in Health (Red-LIRHUS) data, a multi-centric census of students in their first year and fifth year of medicine, from 63 medical schools in 11 countries in Latin America. All students who had indicated wanting to choose a specialty and who chose a specific specialty were considered as participants. Results: Of the 11,072 surveyed, 9,235 indicated wanting to choose a specialty and indicated the name of a specific specialty. The specialties most often chosen in the fifth year were General Surgery (13.0%), Pediatrics (11.3%), Internal Medicine (10.3%) and Obstetrics and Gynecology (9.2%). For women, the top choices were Pediatrics (17.3%), Obstetrics and Gynecology (10.8%), Cardiology (8.9%), General Surgery (8.7%), and Oncology (6.5%). In the adjusted analysis, the female gender was associated with the choice of Gynecology (RP: 2.75; IC95%: 2.24-3.38); Pediatric Surgery (RP: 2.18; IC95%: 1.19-3.99), Dermatology (RP: 1.90; IC95%:1.23-2.93), Pediatrics (RP: 1.83; IC95%: 1.55-2.17), and Oncology (RP: 1.37; IC95%: 1.10-1.71). Conclusions: There is an association between the female gender and the intention to choose Obstetrics and Gynecology, Pediatrics, Pediatric Surgery, Dermatology, and Oncology. We recommend conducting studies that consider other factors that can influence the choice of a medical specialty